Improving student learning outcomes through the application of the revised jigsaw collaborative learning model on impulse and momentum material - Novita Novi Ointu; Muhammad Yusuf; Nova Elysia Ntobuo (Jurnal Pijar Mipa, 2022)
This research aims to improve student learning outcomes by applying the revised jigsaw collaborative learning model. This research is conducted at a public high school (SMA Negeri) in Posigadan, Indonesia. The research subjects are the tenth-grade student of SMA Negeri Posigadan, totaling 17 students. This research is conducted in 1 cycle consisting of 3 meetings. The data collection instruments are tests to measure the learning outcomes, observation sheets of student activities, and learning implementation sheets. Based on the data analysis at cycle 1, findings reveal that the classical completeness is 100% totaling 17 students, student activities account for 87%, obtaining excellent and good criteria, and the learning implementation reaches 94.7%. It signifies that the success indicators of this cycle are well-improve the learning implementation, student activities, and student learning outcomes.